Towards a new generation of policies and investments in agricultural water in the Arab region: fertile ground for innovation. Background paper prepared for the high level meeting on agricultural water policies and investments - Borgomeo, Edoardo; Santos, N. (Food and Agriculture Organization of the United Nations, 2019)
The Arab region needs a new generation of policies and investments in agricultural water. Agricultural water management has always posed challenges and opportunities in the Arab world. However, unprecedented and accelerating drivers such as climate change, population growth, and land degradation make agricultural water management a more urgent priority than ever before. In addition, as part of the 2030 UN Agenda for Sustainable Development, Arab countries have committed to work towards an ambitious set of development targets, the Sustainable Development Goals (SDGs). Unless the right policies and investments are put in place, it will be difficult to achieve the SDGs, including ending hunger and providing clean water and sanitation for all.